DIAGNOSTIC CHARACTERS OF FOUR SPECIES OF FLOURY LICE (PSEUDOCOCCIDAE) IN YUCA CROPS (Manihot esculenta) AND OBSERVATIONS ON SOME OF THEIR NATURAL ENEMIES - CASTILLO, JOSE A.; BELLOTTI, ANTHONY C. (Revista Colombiana de Entomología, 1990)
A comparative morphological description is made between four mealybug species (Homoptera: Pesudococcidae), frequently found feeding on cassava (Manihot esculenta Crantz). Phenacoccus manihoti Matile-Ferrero, is a Neo-tropical species that was inadvertently introduced into Africa where it causes severe damage to cassava; Phenacoccus madeirensis Green and Ferrisia virgata (Cockerell), are two polyphagous species with ample distribution in the world, including Colombia, where cassava is an alternative host; Phenacoccus herreni Cox & Williams, is a species that causes considerable yield loss in cassava in Northeastern South America, from the Northeast of Brazil to the Guyanas, Venezuela and the Eastern plains of Colombia. Complimentary information on the biology, behavior, distribution, and alternative hosts is provided as an aid in the identification and differentiation of each of the species. In addition, important identification and behavioral characteristics of the principal natural enemies are provided.